Repetition in McDonald's Slogan - Amar Fadilah (Universitas PGRI Yogyakarta, 2020)
McDonald’s is one of the fast food companies which used stylistic devices as the language strategy. The stylistic devices implemented on the analysis is repetition. The purposes of the analysis on repetition in the McDonald’s advertising slogan are (1) to identify the type of the repetition and (2) to identify the language unit used in the slogan. This research implemented qualitative method; the method is used to qualify the slogans that consist of repetition. There are 10 data of McDonald’s repetition slogans. The results discover three different types of repetition and two language units used in the repetition of the slogan. The research concludes that repetition is used as a particular strategy in McDonald’s slogan in order not only to attract customer’s attention or convey the message but also to bear in their mind about the image of McDonald’s.McDonald’s is one of the fast food companies which used stylistic devices as the language strategy. The stylistic devices implemented on the analysis is repetition. The purposes of the analysis on repetition in the McDonald’s advertising slogan are (1) to identify the type of the repetition and (2) to identify the language unit used in the slogan. This research implemented qualitative method; the method is used to qualify the slogans that consist of repetition. There are 10 data of McDonald’s repetition slogans. The results discover three different types of repetition and two language units used in the repetition of the slogan. The research concludes that repetition is used as a particular strategy in McDonald’s slogan in order not only to attract customer’s attention or convey the message but also to bear in their mind about the image of McDonald’s.